2009
DOI: 10.3177/jnsv.55.282
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Dihydrocapsaicin and Capsaicin on the Distribution of White Blood Cells in Rats

Abstract: SummaryThe acute effects of dihydrocapsaicin (DHC) and capsaicin (CAP) on the number of white blood cells (WBCs), neutrophils, eosinophils, basophils, monocytes, lymphocytes, T lymphocytes, B lymphocytes and NK cells, and serum corticosterone levels were studied in rats. Male 7-wk-old SD rats were divided into DHC (3.0 mg/kg BW), CAP (3.0 mg/ kg BW) and control (CON) groups. The number of total WBCs was 1.30-1.42 times significantly higher in the DHC group than in the CON group at 6-12 h. The number of neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…The combination of lymphocytes, neutrophil and monocyte together accounts for more than 98% of the number of total peripheral WBCs in rats. 25) In the present study, dexamethasone administration markedly decreased the number of WBCs, lymphocytes and monocyte at 1-3 hr after injection ( Fig. 2A-2C).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The combination of lymphocytes, neutrophil and monocyte together accounts for more than 98% of the number of total peripheral WBCs in rats. 25) In the present study, dexamethasone administration markedly decreased the number of WBCs, lymphocytes and monocyte at 1-3 hr after injection ( Fig. 2A-2C).…”
Section: Discussionmentioning
confidence: 84%
“…1B). 5,[23][24][25][26] Statistical Analyses --Experimental data were presented as mean ± SEM. The effects of dexamethasone on the number of WBCs were evaluated by a two-way analysis of variance (ANOVA) for repeated measures.…”
Section: Fig 1 Experimental Protocol Used In the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Lighting was automatically provided from 8:30-20:30. Animal chow (CE-2 cubic type, CLEA Japan, Inc.) and distilled water were given to the rats ad libitum (17). After the adaptation period, the rats were randomly divided into the DADS-free and DADS-orally administered (doseϭ10, 20, and 40 mg/kg BW) groups (nϭ8-9/group).…”
Section: Methodsmentioning
confidence: 99%
“…1) Recently, we reported that a single administration [dose = 3 mg/kg body weight (BW)] of capsaicinoids such as DHC and CAP to rats decreased significantly the number of total lymphocytes, T-lymphocyte and Blymphocyte without changing the number of natural killer (NK) cells. 8) However, the subacute and chronic effects of capsaicinoids on the number and distribution of white blood cells (WBCs) are still unknown. In the present study, we studied the subacute effects of DHC and CAP on the number of total WBCs, lymphocytes, monocyte, neutrophil, eosinophil and basophil in rats.…”
Section: Introductionmentioning
confidence: 99%